2015
DOI: 10.3233/jad-142265
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Supplemental Macular Carotenoids in Alzheimer's Disease: A Randomized Clinical Trial

Abstract: Supplementation with the macular carotenoids (MZ, Z, and L) benefits patients with AD, in terms of clinically meaningful improvements in visual function and in terms of MP augmentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 49 publications
1
64
0
1
Order By: Relevance
“…Study design, subject recruitment, exclusion criteria, blood sample collection/serum preparation methods as well as baseline/six months carotenoid supplementation statistics for this patient cohort have been previously reported by Nolan et al(see [25], [26]). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Study design, subject recruitment, exclusion criteria, blood sample collection/serum preparation methods as well as baseline/six months carotenoid supplementation statistics for this patient cohort have been previously reported by Nolan et al(see [25], [26]). …”
Section: Methodsmentioning
confidence: 99%
“…They are lipid soluble, are transported principally by lipoproteins and can be broadly classified as either oxygenated xanthophylls or non-oxygenated carotenes [21]. Several authors have shown a significantly lower serum concentration of carotenoids (lutein, zeaxanthin and meso-zeaxanthin) in AD subjects [22], [23], [24] which can be increased after 6 months of supplementation with carotenoids [25].…”
Section: Introductionmentioning
confidence: 99%
“…Weekly intake of carotenoidrich foods (eggs, broccoli, corn, dark green leafy vegetables) was recorded using a dietary LZ screener previously used by our group and developed by Elizabeth Johnson. 33 …”
Section: Demographic Lifestyle Medical and Ophthalmic Assessmentmentioning
confidence: 99%
“…This hypothesis is supported by many lines of investigation employing cell free models, culture systems and epidemiological approaches and clinical trials [3,47] , but sources of stress and types of antioxidants are numerous and the mechanisms whereby antioxidant protection can occur are also many. Of particular relevance to this study are prior investigations in which stress was induced using photic sources, and antioxidant supplementation included the use of macular xanthophylls, especially zeaxanthin, in combination with vitamin E. This combination of antioxidants has been previously shown to synergistically protect against photosensitized (RB-mediated) lipid peroxidation in liposomal model systems [62].…”
Section: Discussionmentioning
confidence: 99%